A Critical Task Need Analysis of English for Room Division Department of Hospitality Industry: Internship Students’ Reflection - Fadilah, Rahmi; Ayudia, Honesty Yonanda; Harmawan, Violintikha; Adzandri, Faraz; Rangkuti, Putri Astri (ETERNAL (English Teaching Journal), 2024)
English for hospitality workers is mostly used in the room division where this section is directly related to guests that includes the realm of housekeeping and front office work. In this study, it will be discussed how the needs analysis of the use of English is taken from the learner approach to the task approach. The purpose of the study is for ensuring that language instruction is relevant, efficient, and tailored to the specific requirements of the hospitality industry, ultimately contributing to the success of both employees and the hotel itself. This research is a mixed method research that uses 74 internship students and 5 hotel workers in the field of human resources as research samples. In this study, it was found that the needs of learners that are important to consider at the beginning are subjective and objective needs, related to their attitudes towards English and their own needs. In the task approach, the learning level is divided according to the target task and task type (basic user, intermediate user, and proficient user) and then the pedagogical aspects are analyzed where students in getting learning should be with authentic and communicative materials and student-centered. In addition, from interview of hotel worker, hotel workers recognize English language proficiency as a fundamental skill that enhances their effectiveness, job satisfaction, and career prospects in the dynamic and diverse hospitality industry